2015
DOI: 10.1007/s10103-015-1832-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level phototherapy on delayed onset muscle soreness: a systematic review and meta-analysis

Abstract: To determine the effectiveness of low-level phototherapy (i.e. light-emitting diode therapy [LEDtherapy] or light amplification by stimulated emission of radiation therapy [LASERtherapy]) on pain, skeletal muscle injury (creatine kinase [CK] levels and edema) and skeletal muscle function (range of movement and strength) in people undergoing an exercise protocol. (Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, PEDro, SciELO and LILACS up to May 2014), we included randomized controlled trials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
35
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 46 publications
1
35
1
Order By: Relevance
“…However, Nampo et al [1] dismissed results of strength from Baroni et al [7] (see Table 1 in Nampo et al [1]), despite authors have highlighted it as the most important finding in that study. Summarily, subjects treated with pre-exercise LLLT had significantly smaller levels of strength loss than those treated with placebo until 48 h post-exercise [7].…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…However, Nampo et al [1] dismissed results of strength from Baroni et al [7] (see Table 1 in Nampo et al [1]), despite authors have highlighted it as the most important finding in that study. Summarily, subjects treated with pre-exercise LLLT had significantly smaller levels of strength loss than those treated with placebo until 48 h post-exercise [7].…”
mentioning
confidence: 85%
“…The recently published systematic review with meta-analysis by Nampo et al [1] about the effects of phototherapy using low-level laser therapy (LLLT) or light emitting diodes therapy (LEDT) on delayed onset muscle soreness (DOMS) was critically reviewed by our research team as we have performed many studies in this specific area of research. The study suggests a conflicting conclusion than the previous released systematic review [2] and a meta-analysis [3] that suggested positive effects of phototherapy (or photobiomodulation therapy) on skeletal muscle performance and recovery.…”
mentioning
confidence: 99%
See 3 more Smart Citations